The Global Digital Divide And Sports Management Under The Sports Professionalism In Algeria - bouaziz sasi (sports creativity, 2025)
The study aimed to clarify the digital divide of the Algerian sports administration in the sports professionalism of Algeria and the management of professional sport in the countries presented by studying this gap and its reality and highlighting the differences between the North and the South. south of the globe, which asks us to talk about the need to reduce the digital divide. The Geneva meeting in 2003 and Tunisia in 2005 are perhaps the most explicit expressions of formal and informal efforts to examine the reality of the digital imbalance and the means to correct it. And through what we saw in the project Algeria e-2013-2008. This reflects the interest of the Algerian government in the need to modernize the government sector and the social, economic, political and technological needs dictated by the Algerian e-strategy aimed at the emergence of the Algerian society of knowledge and knowledge, taking into account the profound and rapid changes in the world. When the descriptive analytical method was used and the questionnaire used as a data collection tool, the study yielded the following results: - the inability of the developing economy to adapt to international conventions such as the GATT; - the stagnation of the economy and the inability to move to a market economy or a competitive economy; - low scientific level and lack of reflection in developing countries; - low technological knowledge and communication with the world and increasing economic and informational poverty; - strengthen the extremist ideology by not interacting with global thinking and generating hatred against developed countries; - Absence of the last channels for the exchange of information between decision-makers indeveloping countries and the transparency of information technology in society.